2016
DOI: 10.1016/j.spacepol.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Space development and space science together, an historic opportunity

Abstract: The national space programs have an historic opportunity to help solve the global-scale economic and environmental problems of Earth while becoming more effective at science through the use of space resources. Space programs will be more cost-effective when they work to establish a supply chain in space, mining and manufacturing then replicating the assets of the supply chain so it grows to larger capacity. This has become achievable because of advances in robotics and artificial intelligence. It is roughly es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 107 publications
0
32
0
2
Order By: Relevance
“…Examples of developments in recent history that might be cited as milestones along this path to the technological posthumanization of societies and the advent of Society 5.0 include the development of the first general-purpose electronic computer (ENIAC) in 1945 (Mauchly 1980); the creation of the first physical artificial neural networks, beginning around 1960 (Adhikari and Kim 2014); the introduction of the first commercial personal computers, in the 1970s (Freiberger and Swaine 2000); the first computer to win a match against a reigning world chess champion, in 1997 (Campbell et al 2002); the establishment in 2001 of what was likely the first fully automated "lights-out factory" that requires no human workers, operated by the Japanese robotics company FANUC (Metzger 2016); the creation of the first commercial deep brain stimulation (DBS) implants, around 2002 (Gardner 2013); the first use of therapeutic social robots (e.g., PARO), around 2004 (Shibata et al 2004); the introduction of robot chefs that prepare food and robot waiters that deliver food to tables in restaurants, around 2006 (Hong 2006;Chen 2016;Nguyen 2016); the growth of the Internet of Things to include roughly 18 billion networked devices (Nordrum 2016), along with the initial mass marketing of voice-activated smart home assistants (Chung et al 2017;LĂłpez et al 2017) and VR game systems (Chang et al 2016;Shelstad et al 2017), all occurring around 2016; and the launch in 2018 of the first driverless car service in the US (Buncombe 2018; Young 2018).…”
Section: The De-posthumanization Of Modern Societies 30 and 40mentioning
confidence: 99%
“…Examples of developments in recent history that might be cited as milestones along this path to the technological posthumanization of societies and the advent of Society 5.0 include the development of the first general-purpose electronic computer (ENIAC) in 1945 (Mauchly 1980); the creation of the first physical artificial neural networks, beginning around 1960 (Adhikari and Kim 2014); the introduction of the first commercial personal computers, in the 1970s (Freiberger and Swaine 2000); the first computer to win a match against a reigning world chess champion, in 1997 (Campbell et al 2002); the establishment in 2001 of what was likely the first fully automated "lights-out factory" that requires no human workers, operated by the Japanese robotics company FANUC (Metzger 2016); the creation of the first commercial deep brain stimulation (DBS) implants, around 2002 (Gardner 2013); the first use of therapeutic social robots (e.g., PARO), around 2004 (Shibata et al 2004); the introduction of robot chefs that prepare food and robot waiters that deliver food to tables in restaurants, around 2006 (Hong 2006;Chen 2016;Nguyen 2016); the growth of the Internet of Things to include roughly 18 billion networked devices (Nordrum 2016), along with the initial mass marketing of voice-activated smart home assistants (Chung et al 2017;LĂłpez et al 2017) and VR game systems (Chang et al 2016;Shelstad et al 2017), all occurring around 2016; and the launch in 2018 of the first driverless car service in the US (Buncombe 2018; Young 2018).…”
Section: The De-posthumanization Of Modern Societies 30 and 40mentioning
confidence: 99%
“…Cluster 4 is quite diverse. We excluded specialized topics in the field of space science (Metzger 2016), mobile services (Qi et al 2014) and football robots (Bi et al 2017). Among representative works within this cluster, a visualization platform for IoT to control and monitor wireless sensor networks (Bi et al 2016), resource allocation (Pillai and Rao 2016) and resource bundling (Guo et al 2016) are examined.…”
Section: Manufacturingmentioning
confidence: 99%
“…60 Based on heritage DOE/NASA designs. 61 Refer to [169] 62 This conversion cycle scales well to high power levels (per Figure 27) and has strong heritage. 63 This conversion cycle is simple, robust, and flight-ready.…”
Section: Cycle: Stirling 63mentioning
confidence: 99%
“…Unit costs for each of these elements through the study period are shown in Table 17 [123] below. 166 http://www.isruinfo.com//docs/LDEM_Draft4-updated.pdf 167 https://ntrs.nasa.gov/archive/nasa/casi.ntrs.nasa.gov/19890004515.pdf 168 https://ntrs.nasa.gov/archive/nasa/casi.ntrs.nasa.gov/20020016967.pdf 169 https://spacecraft.ssl.umd.edu/old_site/academics/484S03/oasis_docs/OASIS_FY01_FINAL.PDF Table 17: Development of Unit Costs for STARLITE 10-yr Lunar Architecture Economic analysis included systems-level, operational and life cycle costing, and modeled the costs and benefits of ISRU vs. an all-expendable baseline for steady-state human missions to the Moon and Mars [123]. It is evident from Figure 74 [123] below that lunar-derived propellant can linearize the rocket equation.…”
Section: Table 16: Production Levels and Unit Costs For Lunar Propellantmentioning
confidence: 99%
See 1 more Smart Citation